Wandel prähistorischer Landschaften.: Kolluvien, Auenlehme und Böden: Archive zur Rekonstruktion vorgeschichtlicher anthropogener Landschaftsveränderungen im Lößgebiet bei Regensburg - Niller, Hans-Peter (ERDKUNDE, 2001)
In the loess area near Regensburg (Bavaria) prehistoric man already caused an important change of relief and soils. Smaller Pleistocene landforms such as dells and minor asymmetric valleys were filled with colluvial deposits and, in general, Pleistocene relief was substantially lowered. At special sites prehistoric land use led to an extreme degradation and erosion of Holocene soils (Orthic Luvisols). According to the examples presented here, there was a high asynchronity of prehistoric landscape evolution, which was due to land-use patterns. Highly differentiated phases of morphodynamic activity (soil erosion) and morphodynamic stability (soil formation) existed in time and space. In the Holocene, there were phases which created short-lived linear erosion features (ephemeral gullies, gullies). These forms were caused by exceptional rainfalls. However, at the moment, it is not possible to connect prehistoric linear erosion with Holocene climate history. The onset of the sedimentation of colluvial deposits took place much earlier than the formation of flood loams. A cascade system illustrates the different ages: at first dells and other minor Pleistocene landforms were filled with colluvial deposits. After the filling of these primary sediment traps, eroded soil material was transported into floodplain areas, thus forming flood loams. So, colluvial deposits represent the oldest prehistoric soil erosion, but flood loams cannot be used to document the onset of anthropogenic landscape change.